Transcriptional Regulation and Signaling of Developmental Programmed Cell Death in Plants - Jiang, Cheng; Wang, Jiawei; Leng, Hua-Ni; Wang, Xiaqin; Liu, Yijing; Lu, Haiwen; Lu, Meng-Zhu; Zhang, Jin (Frontiers in Plant Science, 2021)
Developmental programmed cell death (dPCD) has multiple functions in plant growth and development and is of great value for industrial production. Among them, wood formed by xylem dPCD is one of the most widely used natural materials. Therefore, it is crucial to explore the molecular mechanism of plant dPCD. The dPCD process is tightly regulated by genetic networks and involved in the transduction of signaling molecules. Several key regulators have been identified in diverse organisms and individual PCD events. However, the complex molecular networks controlling plant dPCD remain highly elusive, and the original triggers of this process are still unknown. This review summarizes the recent progress on the transcriptional regulation and signaling of dPCD during vegetative and reproductive development. It is hoped that this review will provide an overall view of the molecular regulation of dPCD in different developmental processes in plants and identify specific mechanisms for regulating these dPCD events. In addition, the application of plants in industrial production can be improved by manipulating dPCD in specific processes, such as xylogenesis.